Pengaruh Model Two Stay Two Stray Modifikasi Social Emotional Learning Terhadap Keterampilan Sosial Siswa - Hamid, Nurul Hikmah Ramadanil; Hidayat, Otib Satibi; Lestari, Ika (Jurnal Ilmiah Global Education, 2025)
This study aims to explore the impact of implementing the Two Stay Two Stray (TSTS) model combined with Social Emotional Learning (SEL) on social skills, taking into account students' levels of self-confidence. The research employed a quantitative approach using a quasi-experimental method with a 2×2 treatment by level design. The sample consisted of 42 fourth-grade students from SD Islam Dwi Matra, South Jakarta, who were divided into two groups: an experimental group that received instruction using the SEL-based TSTS model, and a control group that was taught using the STAD approach. Data collection instruments included a performance assessment to measure social skills and a questionnaire to measure students' self-confidence. The results of the two-way ANOVA analysis indicated a significant difference in social skills between students taught using the SEL-modified TSTS model and those taught using STAD. Furthermore, there was a significant interaction between the learning model and students' self-confidence levels on their social skills. The follow-up Tukey test revealed that the SEL-modified TSTS approach was more effective for students with high self-confidence, while the STAD approach was more suitable for students with low self-confidence. These findings highlight the importance of aligning instructional models with students’ psychological characteristics to maximize the development of social skills at the elementary school level.